2017
DOI: 10.1177/1471301217693867
|View full text |Cite
|
Sign up to set email alerts
|

Voices of Spouses Living with Partners with Neuropsychiatric Symptoms Related to Dementia

Abstract: Persons with dementia, who reside in their own homes, are often cared for by family members. The presence of a family career is said to have a protective effect, postponing admissions to residential care. The majority of persons with dementia develop behavioural and personality changes during the disease trajectory also known as neuropsychiatric symptoms. Quality of life for both the person with neuropsychiatric symptoms and their careers are affected, increasing suffering and risk for hospitalisation and admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Research has found that spouse carers of persons with dementia can report a quality of life that is lower than the person for whom they care (Wadham et al, 2016), and commonly perceive their caring responsibilities as too overwhelming to maintain (Swedish Family Care Competence Centre, 2014). Furthermore, research has shown that carers often do not receive the type of support they want and need (Phillipson, Jones, & Magee, 2014;Tyrrell, Hilleras, Skovdahl, Fossum, & Religa, 2017). In their review of research on spouse carers of persons with dementia, La Fontaine and Oyebode (2014) concluded that the marital relationship is often strained, the carer can feel trapped in their situation, lonely, lacking in support and have no time to take care of their own health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that spouse carers of persons with dementia can report a quality of life that is lower than the person for whom they care (Wadham et al, 2016), and commonly perceive their caring responsibilities as too overwhelming to maintain (Swedish Family Care Competence Centre, 2014). Furthermore, research has shown that carers often do not receive the type of support they want and need (Phillipson, Jones, & Magee, 2014;Tyrrell, Hilleras, Skovdahl, Fossum, & Religa, 2017). In their review of research on spouse carers of persons with dementia, La Fontaine and Oyebode (2014) concluded that the marital relationship is often strained, the carer can feel trapped in their situation, lonely, lacking in support and have no time to take care of their own health.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, spouse carers report feeling that they are losing their partner due to difficulties in sharing thoughts, emotions and experiences, leading to reduced intimacy and a sense that they are no longer married (Eloniemi-Sulkava et al, 2002;Kaplan, 2001;Pozzebon, Douglas, & Ames, 2016). Tuomola, Soon, Fisher, and Yap (2016) found that spouses reported insufficient rest, guilt, a loss of sense of self and an acceptance of their caring role as their destiny, while Tyrrell et al (2017) found that due to the person with dementia's need for constant supervision, spouses' social life and recreational activities were significantly reduced. Other research has similarly found that the lives of spouse carers of persons with dementia become so focused on their caring role that they abandon leisure activities and social relations leading to isolation, distress, self-criticism, guilt, depression and lower life satisfaction (Liu et al, 2017;Pertl, Lawlor, Robertson, Walsh, & Brennan, 2015;Wawrziczny, Pasquier, Ducharme, Kergoat, & Antoine, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Support with daily living, navigating the healthcare system, emotional support, and coping strategies are important issues for family caregivers. Research from Sweden suggests adoption of person-centred approach to meet individual needs of family caregivers of PWD who experience lack of support in dealing with the behavioural and cognitive changes in the PWD that they care for, and their own sense of vulnerability and isolation [13].…”
Section: Support For Family Caregivers Of Pwdmentioning
confidence: 99%
“…All in all, spousal caregivers to partners with dementia who display aggressive behaviors ultimately report feeling a lack of support, isolated, and vulnerable (Tyrrell, Hillerås, Skovdahl, Fossum, & Religa, 2016). Existing research about these civilian caregivers' experiences with, interpretations of, and responses to violence in the caregiving relationship is a helpful supplement to how military caregivers might interpret and respond to violence in situations with their veterans.…”
Section: Ipv In Civilian Familial Caregiving Relationshipsmentioning
confidence: 99%